Incentivizing Physicians' Diagnostic Effort and Test with Moral Hazard and Adverse Selection - David Bardey; Philippe De Donder; Marie-Louise Leroux (CESifo GmbH, 2025)
We study a situation where physicians differing in their degree of altruism exert a diagnostic effort before deciding whether to test patients to determine the most appropriate treatment. The diagnostic effort generates an imperfect private signal of the patient's type, while the test is perfect. At the laissez-faire, physicians exert insufficient diagnostic effort and rely excessively on testing. We show that the first-best allocation (where the degree of altruism is observable) can be decentralized by a payment scheme composed of i) a pay-for-performance (P4P) part based on the number of correctly treated patients to ensure the provision of the optimal diagnostic effort, and of ii) a capitation part to ensure both the optimal testing decision and the participation of physicians. When physicians differ in their (non-observable) degree of altruism, the optimal contract is pooling rather than separating, an instance of non-responsiveness. Its uniform P4P component induces more altruistic physicians to exert a larger diagnostic effort while, to incentivize the second-best optimal testing decision, its capitation component must be contingent on the test cost.
Keywords: D82; D86; I18; 330; diagnostic risk; personalized medicine; non-responsiveness; capitation payment; pay-for-performance; hidden action and hidden information